(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
Occupational health and safety (OHS) education in engineering programs faces persistent challenges in developing students’ risk-based decision-making competencies. Despite established curricula, gaps remain between what is taught and what students can actually apply in professional contexts.